Development of Mobile Media Based on Problem-Based Learning in Basic Computer Network Engineering and Communication Subjects - Latifah Annisa; Nizwardi Jalinus; Yeka Hendriyani; Mukhlidi Muskhir (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to develop mobile learning media specifically designed for basic subjects in Computer Network Engineering and Telecommunications to enhance student motivation and learning outcomes. Utilizing the RD (Research and Development) method, the ASSURE model was employed for development. This model includes analyzing learners, stating objectives, selecting instructional methods, media, and materials, utilizing media and materials, requiring learner participation, and evaluating and reinforcing. The mobile media was tested with 36 students from TJKT Vocational High School in Padang. Data collection instruments included validation sheets, practicality questionnaires, student evaluation questions, and student response questionnaires. Results showed a material expert validity of 0.89 and a media expert validity of 0.94, both indicating high validity. Teacher-assessed practicality scored 90.67, while student assessments scored 86.19, both in the very practical category. Effectiveness was determined by student evaluations, with 88.89% of students achieving competency, indicating high effectiveness. The increase in student learning outcomes was significant, with a gain score of 0.74% in the high category. The T-test revealed a significant difference in pretest and posttest learning outcomes (p-value 0.005). In conclusion, the problem-based learning mobile media developed for basic computer network engineering and telecommunications subjects has been validated, deemed practical, and proven effective for learning. Its implementation is expected to boost student engagement, creativity, and learning outcomes, thereby potentially improving the overall quality of education.